Usher Syndrome in Two Siblings, A Case Report - Teddy Kristiyan; Nadia Artha Dewi; Safaruddin Refa (International Journal of Retina, 2019)
Introduction: Usher Syndrome is a rare genetic disorder involving abnormalities in the retina and hearing, where the patients will experience blindness and hearing loss due to mutations of the gene. Blindness caused by Usher Syndrome has not been prevented until now, but the emphasis is more on focusing early diagnosis, especially patients with Retinitis Pigmentosa. Methods: This Case represent of two siblings with Retinitis Pigmentose (RP) and profound bilateral sensorineural deafness. Diagnosis based on patients decreases of vision since teenagers and worst at night, visual acuity and visual field examination in both patients, Ophthalmoscopic findings, and sensorineural deafness diagnosed by Ear, Nose, and Throat (ENT) department. Electroretinogram (ERG) was not carried out in the two patients because of the limitations of diagnostic facilities. Result: In both eyes of both siblings, ophthalmoscopic evaluation disclosed numerous bone spiculae at peripheral area. Humphrey perimetry showed a tunnel vision. The hearing test also showed a sensorineural hearing loss (SNHL). Conclusion: two affected member of the family were found to exhibit an usher syndrome, this pedigree supports the genetic cotransmission of the traits.